2016
DOI: 10.1093/infdis/jiw249
|View full text |Cite
|
Sign up to set email alerts
|

β-Glucans Are Masked but Contribute to Pulmonary Inflammation DuringPneumocystisPneumonia

Abstract: β-glucans, which can activate innate immune responses, are a major component in the cell wall of the cyst form of Pneumocystis In the current study, we examined whether β-1,3-glucans are masked by surface proteins in Pneumocystis and what role β-glucans play in Pneumocystis-associated inflammation. For 3 species, including Pneumocystis jirovecii, which causes Pneumocystis pneumonia in humans, Pneumocystis carinii, and Pneumocystis murina, β-1,3-glucans were masked in most organisms, as demonstrated by increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…The retention of ␤-glucans in the absence of ␣-glucan, chitin, and mannans (see below) suggests that ␤-glucans are absolutely necessary for the survival of Pneumocystis cysts, supporting ␤-glucans as potential targets for treatment of PCP. Indeed, several studies have shown that inhibitors of ␤-1,3-glucan synthase are highly effective at reducing cyst numbers in animal models of PCP (132,204,216,217,(219)(220)(221). In other fungi, ␤-1,3-glucan is found as a branched polymer with ␤-1,6 side interchains and is covalently linked to other wall components, such as chitin, mannans, and glycoproteins (193,195,222).…”
Section: Genome Featuresmentioning
confidence: 99%
“…The retention of ␤-glucans in the absence of ␣-glucan, chitin, and mannans (see below) suggests that ␤-glucans are absolutely necessary for the survival of Pneumocystis cysts, supporting ␤-glucans as potential targets for treatment of PCP. Indeed, several studies have shown that inhibitors of ␤-1,3-glucan synthase are highly effective at reducing cyst numbers in animal models of PCP (132,204,216,217,(219)(220)(221). In other fungi, ␤-1,3-glucan is found as a branched polymer with ␤-1,6 side interchains and is covalently linked to other wall components, such as chitin, mannans, and glycoproteins (193,195,222).…”
Section: Genome Featuresmentioning
confidence: 99%
“…Two animals with markedly enlarged lungs were excluded from the analysis due to a concern that they were coinfected with another pathogen; inclusion of these animals did not change the results of the statistical analyses. ␤-glucans and may lead to the activation of different pathways from that seen with inhalation of very small numbers of organisms in which, for example, the ␤-glucans in large part are masked (36).…”
Section: Il-17 In Pneumocystis Infectionmentioning
confidence: 99%
“…Consistent with our results, a previous study reported that Pneumocystis cell wall beta‐glucan stimulated ERK phosphorylation and IL‐8 secretion in a human airway epithelial cell line (Carmona, Lamont, Xue, Wylam, & Limper, ). We previously demonstrated that IL‐6 expression was increased in mice with a heavy Pneumocystis infection, and that treatment with caspofungin, a β‐(1,3)‐glucan synthase inhibitor, significantly deceased IL‐6 expression (Kutty et al, ). Although neither IL‐6 nor IL‐8 appear to be critical in controlling Pneumocystis infection (Chen, Havell, Gigliotti, & Harmsen, ), both can exacerbate inflammation associated with Pneumocystis , and have been associated with more severe disease and death in patients with PCP (Chou, Lin, Tsai, & Chang, ; Tasaka et al, ).…”
Section: Discussionmentioning
confidence: 99%